Waiting to get a pension: The impact of pension eligibility on psychological distress - Atalay, Kadir; Staneva, Anita (My University, 2022)
In this paper, we examine how pension eligibility affects the psychological distress levels of older women in Australia by exploiting the exogenous changes in the eligibility ages of the old Age Pension (AP). The unique features of the Australian AP allow us to study the impact of the reform on the non-working, as well as on the working population. The empirical results show that pension eligibility has a modest but consistently beneficial effect on psychological stress levels. Reaching pension eligibility significantly reduces the stress levels of women who were out of the labor force, indicating the positive role of the AP for disadvantaged groups. At the same time, women with strenuous jobs experience a significant improvement in their stress levels when they transit into retirement. We show that an improvement in stress levels accompanies an increase in financial security and improvements in social participation and health behaviors. Our results highlight the potentially overlooked consequences of pension reforms for the well-being of vulnerable populations and for health inequalities across socio-economic groups.
Health Economics
Keywords: Ageing; Health and wellbeing; Income, wealth and finances